2021
DOI: 10.1530/erc-20-0337
|View full text |Cite
|
Sign up to set email alerts
|

B7 immune-checkpoints as targets for the treatment of neuroendocrine tumors

Abstract: The B7 family, and their receptors, the CD28 family, are major immune checkpoints that regulate T-cell activation and function. In the present study, we explore the role of two B7 immune-checkpoints: HERV-H LTR-Associating Protein 2 (HHLA2) and B7 Family Member, H4 (B7x), in the progression of gastrointestinal and pancreatic neuroendocrine tumors (GINETs and PNETs). We demonstrated that both HHLA2 and B7x were expressed to a high degree in human GINETs and PNETs. We determined that the expression of B7x and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Demonstrated the cooperative role of tumor suppressor genes, Men1, Rb1, Pten, and Trp53 in pNET suppression [76] RIP-Tag2; Rabl6 m/m C57BL/6N Insulinoma Loss of oncogenic RABL6A attenuates pNET progression and angiogenesis in RIP-Tag2 mice [77] Pdx1-Cre; Men1 f/f ; B7x KO C57BL/6 Insulinoma Loss of B7x, an immune-checkpoint ligand, reduces islet β-cell proliferation and pNET formation consistent with increased T-cell infiltration [78] (Abbreviations: RIP = rat insulin promoter, MIP = mouse insulin promoter, Tag = T-antigen).…”
Section: Reference Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demonstrated the cooperative role of tumor suppressor genes, Men1, Rb1, Pten, and Trp53 in pNET suppression [76] RIP-Tag2; Rabl6 m/m C57BL/6N Insulinoma Loss of oncogenic RABL6A attenuates pNET progression and angiogenesis in RIP-Tag2 mice [77] Pdx1-Cre; Men1 f/f ; B7x KO C57BL/6 Insulinoma Loss of B7x, an immune-checkpoint ligand, reduces islet β-cell proliferation and pNET formation consistent with increased T-cell infiltration [78] (Abbreviations: RIP = rat insulin promoter, MIP = mouse insulin promoter, Tag = T-antigen).…”
Section: Reference Key Findingsmentioning
confidence: 99%
“…pNETs have low mutational burden and as such, are traditionally perceived to be 'cold' tumors offering limited scope for immunotherapy. Notably, a recent study by Yuan et al, demonstrates that B7x, an immune-checkpoint ligand expressed by tumor cells, suppresses anti-tumor immunity in pNETs and as such, could be an attractive target for (p)NET immunotherapy [78]. The authors demonstrated that genetic ablation or administration of B7x antibody in Men1-deficient mice with insulinomas results in reduced islet cell proliferation and pNET development accompanied by increased T-cell infiltration (Table 2).…”
Section: Heat Shock Protein (Hsp) 90mentioning
confidence: 99%
“…Overexpressed in multiple human cancer types, the prognostic role of HHLA2 remains controversial ( Table 1 ). Several studies indicated that overexpression of HHLA2 in tumour cells was associated with unfavorable clinical outcomes and shorter survival rate in patients with prostate cancer, 26 neuroendocrine tumours, 27 hepatocellular carcinoma, 28 , 29 , 30 lung adenocarcinoma, 31 , 32 , 33 , 34 gastric cancer, 35 oral squamous cell carcinoma, 36 bladder urothelial carcinoma, 37 intrahepatic cholangiocarcinoma, 38 colorectal carcinoma, 39 , 40 osteosarcoma, 41 and triple negative breast cancer. 17 On the contrary, HHLA2 was a protective factor predicting low mortality rate in patients with pancreatic cancer, 14 , 42 , 43 epithelial ovarian cancer, 44 malignant glioma, 45 and recurrent or unresectable advanced gastric cancer.…”
Section: Role Of Hhla2 In Cancer Developmentmentioning
confidence: 99%
“… Tumour type Year Research object/Numbers HHLA2 expression Conclusions Refs. Prostate cancer 2021 Patient tumour samples, N = 239 Tumour cells High HHLA2 expression was an independent prognostic predictor for prostate cancer, and was negatively correlated with CD TILs 26 Neuroendocrine tumours 2021 Patient tumour samples, N = 37 Tumour cells High HHLA2 expression was correlated with high tumour grade and metastasis 27 Colorectal cancer 2021 Patient tumour samples, N = 214 Tumour cells HHLA2 expression was low in colorectral cancer and appeared to have no influence on clinical outcomes. 40 Hepatocellular carcinoma 2021 Patient tumour samples, N = 205 Peri-tumour region of HCC tissues HHLA2 expression in the peri‑tumour region was an independent prognostic factor for OS, and was negatively correlated with PD-L1 28 Patient tumour samples, N = 55 Tumour cells Higher expression of HHLA2 protein was associated with advanced cancer stage, tumour differentiation, and invasion of adjacent structures 29 Patient tumour samples, N = 202 Tumour cells HHLA2 level was a independent worse prognostic factor and affected the tumour microenvironment 30 Epithelial ovarian cancer 2021 Patient tumour samples, N = 64 Tumour cells HHLA2 was correlated with high CD TIL levels and tumour differentiation; and predicted improved survival in ovarian cancer 44 Lung adenocarcinoma 2021 …”
Section: Role Of Hhla2 In Cancer Developmentmentioning
confidence: 99%
“…Currently, more immune checkpoints are being elaborated upon in tumor studies, such as the B7 family, T cell immunoglobulin, and mucin domain-containing protein 3 (TIM-3), CD47, and CD74. HERV-H LTR-associating protein 2 and B7 family member H4, as two B7 family immune checkpoints, are richer in GEP-NETs and are associated with a high tumor grade and lymph node metastasis rate [ 76 ]. Additionally, CD47 and CD74 are highly abundant, but PD1, PD-L1, and TIM-3 are lacking in ileal NENs [ 45 ].…”
Section: Immune Checkpointsmentioning
confidence: 99%